2020
DOI: 10.1016/j.xjon.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The association of acute kidney injury with hospital readmission and death after pediatric cardiac surgery

Abstract: Background: Acute kidney injury (AKI) in children undergoing cardiac surgery (CS) is strongly associated with increased hospital mortality and length of stay. The association of AKI with postdischarge outcomes is unclear. We evaluated the association of AKI with all-cause readmissions and death within 30 days and 1 year of CS discharge. Methods: This was a prospective, 3-center cohort study of children after CS with cardiopulmonary bypass. The primary exposures were postoperative stage 1 AKI and stage 2 AKI de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…This has not only allowed us to identify AKI as an important risk factor for poor long-term outcomes, but it has also allowed us to quantify the magnitude of risk of developing these outcomes. Over the past 5 years, more data has been published beyond early mortality (within 28-days) describing both medium (1-2 year) (6,15,16,18) and long-term mortality risk (>3 years) (17,19). Importantly, only two studies evaluated post-discharge mortality (i.e., excluded hospital mortality from the index admission).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This has not only allowed us to identify AKI as an important risk factor for poor long-term outcomes, but it has also allowed us to quantify the magnitude of risk of developing these outcomes. Over the past 5 years, more data has been published beyond early mortality (within 28-days) describing both medium (1-2 year) (6,15,16,18) and long-term mortality risk (>3 years) (17,19). Importantly, only two studies evaluated post-discharge mortality (i.e., excluded hospital mortality from the index admission).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies specifically focused on mortality in children with AKI following cardiac surgery. In a multicenter study of over 400 patients, Nune et al found that children with severe AKI post-cardiac surgery had over 11 times higher risk of mortality 30-day after surgery, following adjustment for age, surgical risk score, cardiopulmonary bypass time, and cyanotic heart disease (18). In a similar-sized population, Hirano…”
Section: Cardiac Surgery Populationmentioning
confidence: 99%
See 3 more Smart Citations